2002
DOI: 10.1658/1100-9233(2002)013[0461:papogf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Present and past old-growth forests of the Lake Tahoe Basin, Sierra Nevada, US

Abstract: We described 38 relictual old-growth stands -with data on the mortality, regeneration, floristic richness, fuel load and disease incidence in our study area in the Tahoe Basin of California and Nevada. The stands are within the lower and upper montane zones (1900-2400 m a.s.l.) and they are rare, occupying < 2% of the land in the Basin's watershed. Correlation matrices and ANOVAs of forest types and conifer species with environmental gradients revealed significant relationships with elevation, distance east of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 16 publications
7
64
0
Order By: Relevance
“…Jeffrey pine-mixed conifer forests in this study had similar snag densities as those reported in Ganey (1999) and are the lower range of Barbour et al (2002) recommendation, but in 1998 there were no snags in 35% of plots, and after a severe drought that significantly increased snag abundance, there were still zero snags on 28% of plots. Average snag density of 5/ha is similar to that found in other pine-dominated forests before harvesting or fire suppression (Table 4) but this density was produced by approximately 60% of the inventoried area in this study.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Jeffrey pine-mixed conifer forests in this study had similar snag densities as those reported in Ganey (1999) and are the lower range of Barbour et al (2002) recommendation, but in 1998 there were no snags in 35% of plots, and after a severe drought that significantly increased snag abundance, there were still zero snags on 28% of plots. Average snag density of 5/ha is similar to that found in other pine-dominated forests before harvesting or fire suppression (Table 4) but this density was produced by approximately 60% of the inventoried area in this study.…”
Section: Discussionsupporting
confidence: 71%
“…There are very few small, dead trees in the SSPM (only 7% with DBH < 10 cm). This is in contrast to ponderosa pine and mixed conifer forests in Arizona and California, where current snag populations are dominated by small snags (Ganey, 1999;Barbour et al, 2002). Fire suppression has increased tree density and canopy cover in many western US forests and the resulting competition has probably contributed to the high number of small dead tress.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The introduction of grazing, decimation of the Native American population, and more recent fire suppression policies however, resulted in fire exclusion and increased tree density, fuel accumulation, and fuel continuity on the forest floor (Skinner and Chang, 1996;McKelvey and Busse, 1996;Bradley and Tueller, 2001). Fire exclusion has promoted uniform tree age and structural distributions, and has altered stand composition by allowing shade tolerant species such as firs (Abies) to crowd out shade intolerant species such as pines (Pinus) (Parsons and DeBennedetti, 1979;Barbour et al, 2002). The unnatural accumulation of fuels and changes to stand structure are feared to have detrimental effects on the ecosystem while also greatly increasing the risk of high intensity crown fires.…”
Section: Introductionmentioning
confidence: 99%
“…It also protects young trees from wind or ice abrasion (Marr, 1977;Hadley and Smith, 1989;Engelmark et al, 1998) and needle damage due to spring frost (Wardle, 1968;Hänninen, 1996). Deep and persistent snow cover in spring increases water availability in early summer, which in combination with high summer temperatures was found to increase the elevation of treeline in some subalpine forests (Hessl and Baker, 1997) or to favor tree growth in others (Barbour et al, 2002). However, late-laying snow in spring shortens the growing season (Walsh et al, 1994;Alftine and Malanson, 2004), increases the risk of black snow mold (Herpotrichia nigra R. Hartig) infection (Simms, 1967), and may lead to the drowning of seedlings by snow (Wardle, 1968).…”
Section: Introductionmentioning
confidence: 99%